KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN KEFEKTIFAN KINERJA GURU TERSERTIFIKASI DI MTs NU 02 GRINGSING KABUPATEN BATANG - NAFI’AN NAFI’AN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The principal was an educational leader who has a role in developing the quality of education in schools. The development of work spirit, harmonious cooperation, interest in the development of education, and the development of the quality of the teachers they lead were largely determined by the quality of coaching and leadership of the principal. The principal also carries out coaching, facilitating, and providing broad opportunities as enthusiasm and encouragement to certified teachers. It also aimed to carry out professional development activities through various educational and training activities. In this study, the researcher used a qualitative descriptive approach. This qualitative descriptive approach did not always look for cause and effect but sought to understand certain situations. Researchers tried to understand and appreciate the leadership role of the madrasa principal in increasing the effectiveness of certified teacher performance at MTs NU 02 Gringsing, Batang Regency. This study also used teacher resource data as the source whose research results are in the form of words or statements that are by actual or natural conditions. The implementation of the process of implicating the leadership of the madrasah principal, the principal's leadership strategy in anticipating obstacles, to the success of the madrasah's leadership in increasing the effectiveness of teacher performance are essentially actions and policies that must be taken by the madrasah principal fairly and wisely to direct and assist teachers to improve their professionalism. So that in the end, they would become respected, respected figures, have adequate qualifications, their insights and skills continue to increase and become good role models for students. The leadership strategy of the head of MTs NU 02 Gringsing in carrying out learning evaluations, especially certified teachers, is also going well. It was done by the head of the madrasa to directly observe the learning process carried out by certified teachers starting from pre-learning, core activities, and closing lessons. After the supervision and evaluation of certified teachers at MTs NU 02 Gringsing, both related to pedagogy and administration, as well as the performance of certified teachers, the effectiveness of the teacher's performance went well. ABSTRAKKepala sekolah adalah pemimpin pendidikan yang mempunyai peranan sangat besar dalam mengembangkan kualitas pendidikan di sekolah. Berkembangnya semangat kerja, kerjasama yang harmonis, minat terhadap perkembangan pendidikan serta perkembangan kualitas guru-guru yang dipimpinnya banyak ditentukan oleh kualitas pembinaan dan kepemimpinan kepala sekolah. Kepala sekolah juga melaksanakan pembinaan, memfasilitasi dan memberikan kesempatan yang luas serta semangat dan dorongan kepada para guru tersertifikasi. Hal ini juga bertujuan untuk dapat melaksanakan kegiatan pengembangan profesi melalui berbagai kegiatan pendidikan dan pelatihan (workshop). Pada penelitian ini peneliti menggunakan pendekatan deskriptif kualitatif. Pendekatan deskriptif kualitatif ini tidak selalu mencari sebab akibat namun lebih berupaya memahami situasi tertentu. Peneliti berusaha memahami dan menghayati peran kepemimpinan kepala madrasah dalam meningkatkan keefektifan kinerja guru tersertifikasi di MTs NU 02 Gringsing Kabupaten Batang. Penelitian ini juga menggunakan data sumber daya guru sebagai sumber utama yang hasil penelitiannya berupa kata-kata atau pernyataan yang sesuai dengan keadaan sebenarnya atau alamiah. Pelaksanaan proses implikasi kepemimpinan kepala madrasah, strategi kepemimpinan kepala madrasah mengantisipasi hambatan, hingga keberhasilan kepemimpinan kepala madrasah dalam meningkatkan keefektifan kinerja guru pada hakikatnya adalah tindakan dan kebijakan yang harus diambil kepala madrasah secara adil dan bijksana dalam rangka mengarahkan dan membantu guru untuk meningkatkan profesionalismenya. Sehingga pada akhirnya meraka akan manjadi sosok yang dihormati, disegani, memiliki kualifikasi yang memadai, wawasan dan skillnya terus meningkat serta menjadi panutan yang baik bagi peserta didik. Strategi kepemimpinan kepala MTs NU 02 Gringsing dalam melaksanakan evaluasi pembelajaran, terutama guru tersertifikasi juga berjalan baik. Hal ini dilakukan oleh kepala madrasah untuk mengamati langsung proses pembelajaran yang dilakukan oleh guru tersertifikasi mulai dari pra pembelajaran, kegiatan inti dan penutup pembelajaran. Setelah diadakan Supervisi dan evaluasi terhadap guru tersertifikasi di MTs NU 02 Gringsing baik berkaitan dengan pedagogik dan administrasinya, maupun kinerja guru tersertifikasi maka keefektifan kinerja para guru tersebut berjalan dengan baik.